Реактивність і взаємодія глутатіону еритроцитів і кисневотранспортної функції крові при гемічній гіпоксії гемолітичного генезу - Лановенко, І.І.; Гащук, Г.П. (Доповіді НАН України, 2022)
Глутатіон (GSH) є універсальним регулятором загального і кисневого гомеостазу. З огляду на поліпротекторні
властивості GSH актуальними є дослідження його ролі в генезі гіпоксичних станів і особливо гемічної гіпоксії
при анеміях. У статті висвітлені результати дослідження змін і взаємодії глутатіону еритроцитів та
кисневотранспортної функції крові при гемічній гіпоксії гемолітичного генезу.
В експерименті на щурах відтворювали модель гемічної гіпоксії (ГГ) гемолітичного генезу. В умовах ГГ
застосовували вплив на метаболізм GSH: стимуляцію за допомогою його синергіста цистеаміну і донора
GSH глутаргіну; пригнічення за допомогою його антагоніста GSH діетилмалеату. Визначали показники
гемограми, мієлограми, обміну заліза, в еритроцитах крові — вміст відновленого (GSH) та окисненого (GSSG)
глутатіону і активність глутатіонредуктази (GR), гемічну гіпоксію за показниками кисневотранспортної
функції (КТФ) крові. Встановлено порушення КТФ крові (зменшення доставки і споживання О₂, метаболічний ацидоз) і
значне зниження вмісту (у 2,85 раза) глутатіону (GSH) і активності (у 4,89 раза) GR в еритроцитах крові.
Пригнічення утворення GSH (за допомогою діетилмалеату) призводить до поглиблення недостатності
GSH і порушень КТФ крові; стимуляція утворення GSH (за допомогою цистеаміну і глутаргіну) підвищує
продукцію GSH, підсилює активність GR та відновлює КТФ крові. Обґрунтована можливість регуляції КТФ
крові і корекції гемічної гіпоксії за допомогою регуляції метаболізму глутатіону. Glutathione (GSH) is an universal regulator of biochemical, physiological and oxygen homeostasis in humans
and animals. The state of the erythrocyte glutathione system significantly affects hemoglobin activity and the
mechanisms of regulation of the oxygen blood transport function (OBTF) of the blood in general. The studies of
the functional significance and role of GSH in the genesis of hypoxic conditions and, particularly, hemic hypoxia
in anemia are relevant given the polyprotective properties of GSH. The purpose of the work is to investigate
changes and the interaction of erythrocyte glutathione and the the oxygen blood transport function during hemic
hypoxia of hemolytic genesis.
In a laboratory rats experiment, a model of hemic hypoxia (HH) of hemolytic (use of phenylhydrazine)
genesis was reproduced. Under the conditions of HH, effects on the metabolism of GSH were used: stimulation
of the formation of cysteamine (CA) synergist and GSH donor glutargin using GSH synergist; inhibition of a
GSH diethylmaleate antagonist. Arterial and mixed venous blood was used for analysis. The definitions of the
investigated parameters were carried out in the initial state and after exercising of experimental effects. The
following indices were determined: hemogram indicators, bone marrow cell composition and iron metabolism
parameters; the quantity of reduced (GSH) and oxidized (GSSG) glutathione and the activity of the GSH
enzyme glutathione reductase (GR) in blood red blood cells; indicators of oxygen blood transport function
(OBTF) — parameters for hemic hypoxia.
In experiments on rats with modeling haemic hypoxia of hemolytic genesis, the damage of OBTF (delivery
and use O₂ decrease, metabolic acidosis) and a significant decrease in the content (by 2,85 times) of the glutathione
(GSH) and activity (by 4,89 tim es) of the GR in erythrocytes of blood are determined. Inhibition of the generation
of GSH (by means of diethylmaleate) increases the GSH deficiency and OBTF damages; and the activation of
the generation of GSH (by means of cysteamine and glutarine) increases production GSH, it strengthens activity
GR and restores OBTF. The high sensitivity and efficiency of regulation of the oxygen blood transport function
under anemia has been established using targeted effects on glutathione metabolism. The possibility of haemic
hypoxia correctoin by means of the use of glutathione and its donors is grounded.